ANALISIS KEPUASAN KONSUMEN PT. KALTRABU INDAH BANJARMASIN - Rahmat Hilmi; Anthonius Karsudjono (Kresna Bina Insan Prima, 2020)
The purpose of this study was to determine the effect of the independent variable Service Quality consisting of Physical Evidence, Reliability, Responsiveness, Assurance and Empathy both simultaneously and partially on the dependent variable Consumer Satisfaction. And want to know the dominant variables that affect Consumer Satisfaction. The data used is the result of distributing questionnaires to respondents who used the services of PT. Kaltrabu Indah Banjarmasin. The sample selection technique is Accindental Sampling with a total of 60 consumers. Data processing techniques using SPSS (Statistical Package for the Social Sciences). The results showed that simultaneously the variables Physical Evidence, Reliability, Responsiveness, Assurance and Empathy had a significant effect on the purchasing decision variables of PT. Kaltrabu Indah Banjarmasin Branch of 25,515. Partially only the Reliability variable 3,177 (Sig.0,002), Guarantee 2,340 (Sig. 0,023) and Empathy 2,661 (0,010) affect the customer satisfaction of PT. Kaltrabu Indah Banjarmasin. While the Physical Evidence variable 1.983 (Sig. 0.053) and Responsiveness 0.901 (Sig.0.372) did not significantly influence the consumer satisfaction of PT. Kaltrabu Indah Banjarmasin. The dominant influential variable is Reliability with a Standardized Coefficients Beta value of 0.415, meaning that according to consumers' perception the reliability factor becomes something that is considered very important in an effort to create customer satisfaction when using the services of PT. Kaltrabu Indah Banjarmasin. Referring to the terminated Coefficient (R Square) of 0.703, the customer satisfaction of PT. Kaltrabu Indah Banjarmasin of 70.3% is influenced by physical evidence, reliability, responsiveness, assurance and empathy variables. While the remaining 29.7% of customer satisfaction is influenced by other variables not included in this study.